Parental Awareness Regarding Shaken Baby Syndrome and Associated Factors in Jordan - Ali Bani-Ahmed; Roqaya Al-Bawaneh; Eihab Khasawneh; Alham Al-Shorman; Hasan Al-Omari (Jordan University of Science and Technology, 2023)
Background: Shaken Baby Syndrome (SBS) is a form of physical child abuse by parents that may cause long-term brain damage or death. Objectives:  To evaluate the awareness of Shaken Baby Syndrome among Jordanian parents and the risk factors associated with it. Methods: an online designed questionnaire consisted of 3 sections: demographic characteristics, knowledge of shaken baby syndrome, and parental psychological distress. Results: the sample size was 306 participants. Over two-thirds (67.65%) of parents were unaware of Shaken Baby Syndrome and 68.30% reported shaking their children. Detailed frequency analysis showed that among the 67.65 % unaware of Shaken Baby Syndrome, 48.37% reported “Yes” for shaking, especially those aged 30 and above. Furthermore, 67.65 % reported having stress and anxiety, and among those, 49.35% reported “Yes” for shaking the baby, especially those aged 30 and above. The results were supported by the significant correlation between study variables of age, Shaken Baby Syndrome awareness, stress/anxiety, and the action of shaking (p< 0.05). Conclusion: A serious lack of awareness among Jordanian parents about Shaken Baby Syndrome. Risk factors associated with Shaken Baby Syndrome were anxiety/stress especially those aged above 30 yrs. old. SBS and stress/anxiety educational programs are needed to address Shaken Baby Syndrome and prevent possible future complications. Implications for nursing and rehabilitation: The findings of the current study support the role of educational programs on the level of Shaken Baby Syndrome knowledge and awareness among parents and caregivers, which could be a mutual responsibility of rehabilitation team members working in pediatrics units.